A Brazilian multicentre study of 2, 497 isolated cases of odontogenic keratocysts. (14th February 2020) - Schuch, Lauren Frenzel; de Arruda, José Alcides Almeida; Mosconi, Carla; Kirschnick, Laura Borges; Pinho, Rodrigo Finger de Carvalho; Viveiros, Stephanie Kenig; Abreu, Lucas Guimarães; do Amaral‐Silva, Gleyson Kleber; da Silva, Leorik Pereira; Martins‐Chaves, Roberta Rayra; Vasconcelos, Ana Carolina Uchoa; Gomes, Ana Paula Neutzling; et al.
Abstract: We present the frequency of cases of isolated odontogenic keratocysts submitted to microscopic examination at 10 Brazilian referral centres in Oral and Maxillofacial Pathology. In a retrospective (1953–2017) analysis, data on clinicoradiographic features and treatment of these lesions were collected and analysed descriptively. Among the 258, 867 cases retrieved, 2, 497 (0.96%) were isolated odontogenic keratocysts. In summary, an overview of individuals affected with isolated odontogenic keratocysts is reported herein. This lesion showed predilection for the posterior mandible of young adult men.